2021
DOI: 10.1242/jeb.242836
|View full text |Cite
|
Sign up to set email alerts
|

Flight altitude dynamics of migrating European nightjars across regions and seasons

Abstract: Avian migrants may fly at a range of altitudes, but usually concentrate near strata where a combination of flight conditions is favourable. The aerial environment can have a large impact on the performance of the migrant and is usually highly dynamic, making it beneficial for a bird to regularly check the flight conditions at alternative altitudes. We recorded the migrations between northern Europe and sub-Saharan Africa of European nightjars Caprimulgus europaeus to explore their altitudinal space use during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Previous research has demonstrated that the selection of flight altitudes may be key in achieving optimal wind support and play an important role in successfully surpassing ecological barriers [ 22 ]. Also, a recent study on European nightjars has shown that altitude shifts are frequent during migration [ 68 ], supporting the high within-season variation in flight heights we found for Caspian terns.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research has demonstrated that the selection of flight altitudes may be key in achieving optimal wind support and play an important role in successfully surpassing ecological barriers [ 22 ]. Also, a recent study on European nightjars has shown that altitude shifts are frequent during migration [ 68 ], supporting the high within-season variation in flight heights we found for Caspian terns.…”
Section: Discussionsupporting
confidence: 88%
“…Of the 16 deployments in 2019, we were only able to recover one multi-sensor logger due to the COVID-19 pandemic preventing the organization of extensive fieldwork in 2020 and 2021. The recovery rate of 15%, although low, lies within the variation in recovery rates in Western European populations where trapping efforts have been constant across years (Norevik et al 2021), and can most likely be attributed to bad weather conditions during a 2-week trapping session in Mongolia (July 2019). The two loggers recovered in 2019 recorded partial migration cycles, stopping 17 days and 58 days after departure from the wintering site.…”
Section: Resultsmentioning
confidence: 91%
“…First, we used the activity data to determine stationary periods, defined as periods of minimum 12 h during which a bird stays within the same location. As nightjars use flapping flight for migration (Norevik et al 2021), we used an automated k-means classification algorithm to classify periods of flapping flight as migratory flight. Since the pressure analysis relies on high precision of this classification, we manually edit the activity and the pressure timeseries following the recommendation from Nussbaumer et al (2022b).…”
Section: Geolocationmentioning
confidence: 99%
“…To maximise the recapture probability of birds with tags also birds in proximity to the territory of the deployment site were targeted for trapping during the following year(s). For more information regarding recapture rates of tagged nightjars within the study population see Norevik et al (2021).…”
Section: Trapping and Taggingmentioning
confidence: 99%